2014
DOI: 10.1038/ncomms4201
|View full text |Cite
|
Sign up to set email alerts
|

Non-hysteretic colossal magnetoelectricity in a collinear antiferromagnet

Abstract: The manipulation of magnetic ordering with applied electric fields is of pressing interest for new magnetoelectric devices and information storage applications. Recently, such magnetoelectric control was realized in multiferroics. However, their magnetoelectric switching is often accompanied by significant hysteresis, resulting from a large barrier, separating different ferroic states. Hysteresis prevents robust switching, unless the applied field overcomes a certain value (coercive field). Here we address the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 43 publications
11
129
2
Order By: Relevance
“…1 . Reflectance measurements were performed using a series of spectrometers in the ab-plane and along the c-axis between 5 and 300 K. A Kramers-Kronig analysis was used to obtain the optical constants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . Reflectance measurements were performed using a series of spectrometers in the ab-plane and along the c-axis between 5 and 300 K. A Kramers-Kronig analysis was used to obtain the optical constants.…”
Section: Methodsmentioning
confidence: 99%
“…Ni ions have the outer shell electronic configuration t 6 2g e 2 g and spin S = 1, whereas Te is non-magnetic. 1,4 This system thus provides an opportunity to examine (i) magnetoelectric and magnetoelastic coupling when magnetic order develops in a polar lattice and (ii) how transition metal centers mix with non-magnetic ions that have large spin-orbit coupling. The complex magnetism also provides a framework that motivates the search for new high field phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial inversion symmetry is broken and the electric polarization points along the c axis, as in Ca 3 ðCo; MnÞO 6 [10,14]. It was found that NTO undergoes a second-order spin-flop (SF) transition at a critical field H c1 ∼9 T, which accompanies a large ME effect [15]. Here, symmetric exchange striction at the SF transition distorts the polar crystal structure to modify the electric polarization.…”
mentioning
confidence: 99%
“…The ME coefficient (α ≡ dP=dH) is as high as 1300 ps=m at H c1 , without any magnetic hysteresis. However, a phenomenological model with only two magnetic sublattices was implemented to describe the polarization change at the SF transition [15], whereas a full description of NTO requires a model with six different magnetic sublattices and several competing exchange interactions between them [13].…”
mentioning
confidence: 99%